Time of parenteral nutrition in paediatric critical care patients, prior nutritional status probably makes the difference? - Balaguer, Mònica; Jordan, Iolanda (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
It is well known that a delay in nutrient administration in the critical patient leads to a poor prognosis (1-4). It can induce an increase in nosocomial infections, mechanical ventilation duration, intensive care unit (ICU) length of stay (LOS), and mortality. In paediatrics there are only few clinical trials that have systematically analysed the importance of good nutrition in the pediatric critical patient’s outcome (5).